Preparation and application of petal-like oxygen-pyrrolic nitrogen co-modified nitrogen-doped carbon supported copper monatomic catalyst

CN123018000APending Publication Date: 2026-10-30SHANDONG UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611256638.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-19
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0005]为解决现有技术中铜基硝酸根还原电催化剂活性位点不足、形貌可控性差及配位环境难以精准调控的问题,本发明的第一个目的为提供一种花瓣状氧-吡咯氮共修饰氮掺杂碳载铜单原子催化剂制备方法,所述催化剂的制备方法包括以下步骤:

Benefits of technology

[0025]如本发明的花瓣状氧-吡咯氮共修饰氮掺杂碳载铜单原子催化剂,应用于电催化还原反应中,所述电催化还原反应包括硝酸根还原反应、析氢反应或二氧化碳还原反应中的至少一种。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123018000A_ABST
    Figure CN123018000A_ABST
Patent Text Reader

Abstract

The application relates to the technical field of catalysts and provides a petal-shaped oxygen-pyrrole nitrogen co-modified nitrogen-doped carbon copper monatomic catalyst preparation and application, which comprises the following steps: carrying out free radical copolymerization reaction on cyano-containing olefinic unsaturated monomers and acrylamide monomers in acetone, taking azobisisobutyronitrile as an initiator, heating reaction under inert gas protection, drying after reaction, and obtaining copolymer powder; pre-oxidizing and cyclizing the copolymer powder, increasing the temperature to a pre-oxidation temperature at a preset temperature increasing rate and keeping the temperature, and obtaining pre-oxidized and cyclized powder; dispersing the pre-oxidized and cyclized powder in methanol, adding copper salt, removing the solvent after stirring and mixing, and obtaining a precursor; carrying out high-temperature carbonization on the precursor under inert gas protection, obtaining the catalyst, taking cyano-containing olefinic unsaturated monomers-acrylamide as a carbon precursor, and realizing uniform loading of Cu monatomic on a nitrogen-doped carbon matrix through a pre-oxidation cyclization-copper salt loading-high-temperature carbonization process route.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of catalyst technology, and in particular to the preparation and application of a petal-shaped oxygen-pyrrole nitrogen co-modified nitrogen-doped carbon-supported copper single-atom catalyst. Background Technology

[0002] The microstructure of a catalyst has a decisive influence on its electrocatalytic performance. Three-dimensional petal-like structures, due to their large specific surface area, sufficient exposure of active sites, and short mass transport pathways, can significantly improve the efficiency of electrocatalytic reactions and have become a research hotspot in the field of electrocatalyst morphology design in recent years. However, most existing methods for preparing three-dimensional petal-like catalysts involve complex synthesis conditions (such as high-temperature, high-pressure hydrothermal or solvothermal reactions, precise pH adjustment, or slow nucleation and growth control). The formation of the morphology is extremely sensitive to reaction parameters, resulting in poor batch-to-batch reproducibility. Furthermore, the size, lamellar thickness, and degree of opening and closing of the obtained petal structure are difficult to precisely control, severely restricting their large-scale preparation and practical application.

[0003] Polyacrylonitrile (PA) is an excellent polymer precursor with outstanding advantages such as good thermal stability, high carbon yield, easy processing and molding, and high nitrogen content. After carbonization, it can form a nitrogen-doped conductive carbon framework in situ, endowing the material with good conductivity and the ability to anchor metal species while maintaining structural integrity. More importantly, PA-based polymers exhibit self-assembly behavior under specific polymerization conditions, and their formation of three-dimensional hierarchical structures can be induced by controlling polymerization parameters. This provides an ideal platform for template-free construction of petal-like morphologies.

[0004] On the other hand, relying solely on morphology optimization is insufficient to fully unlock the performance potential of catalysts; precise control of the electronic structure of the active center is equally crucial. Constructing specific coordination environments through heteroatom doping (such as N and O) can effectively regulate the electron density and intermediate adsorption energy of the metal active center, thereby enhancing intrinsic catalytic activity. However, current coordination control of copper-based catalysts is mostly focused on CO2 reduction, and often employs bottom-up precursor pyrolysis methods, making it difficult to precisely control the doping ratio and spatial distribution of nitrogen (pyridine nitrogen, pyrrole nitrogen) and oxygen, resulting in insufficient tunability and reproducibility of catalytic performance. Research combining morphology engineering with coordination environment control is even more scarce. Summary of the Invention

[0005] To address the problems of insufficient active sites, poor morphology controllability, and difficulty in precisely controlling the coordination environment in existing copper-based nitrate reduction electrocatalysts, the first objective of this invention is to provide a method for preparing a petal-shaped oxygen-pyrrole nitrogen co-modified nitrogen-doped carbon-supported copper single-atom catalyst. The catalyst preparation method includes the following steps:

[0006] A free radical copolymerization reaction was carried out in acetone using cyano-containing olefinic unsaturated monomers and acrylamide monomers, with azobisisobutyronitrile as the initiator. The reaction was carried out under inert gas protection and the reaction was heated. After the reaction was completed, the copolymer powder was obtained by drying.

[0007] The copolymer powder is subjected to pre-oxidation cyclization treatment by raising the temperature to the pre-oxidation temperature at a preset heating rate and holding it at the temperature, so that the copolymer powder undergoes cyclization crosslinking and stabilization reactions to obtain pre-oxidized cyclized powder.

[0008] The pre-oxidized cyclized powder was dispersed in methanol, copper salt was added, and after stirring and mixing, the solvent was removed to obtain the precursor.

[0009] The precursor was carbonized at high temperature under inert gas protection to obtain a petal-shaped oxygen-pyrrole nitrogen co-modified nitrogen-doped carbon-supported copper single-atom catalyst.

[0010] This invention employs a bottom-up free radical copolymerization strategy, using cyano-containing olefinic unsaturated monomers as the base framework. Acrylamide is introduced as a comonomer and oxygen source during the polymerization stage, and the two copolymerize to form an oxygen-containing copolymer precursor. By controlling the polymerization conditions, the polymer chains are induced to self-assemble into a three-dimensional petal-like structure. The polymerization mechanism is as follows:

[0011]

[0012] Acrylamide is embedded in the polyacrylonitrile backbone in the form of copolymer units containing amide side groups, allowing oxygen atoms to be introduced into the polymer chain through the amide side groups. This oxygen-containing copolymer undergoes pre-oxidative cyclization treatment in an air atmosphere, where the cyano side groups of the acrylonitrile units undergo cyclization and dehydrogenation reactions, crosslinking to form a heat-resistant ladder-shaped pyridine ring structure. The amide side groups of the acrylamide units undergo deamination and partial decomposition under thermal action, with their carbonyl oxygen retained in situ and doped into the carbon-nitrogen framework. Finally, after high-temperature carbonization, a nitrogen-doped carbon substrate with oxygen-pyrrole nitrogen co-modification retaining a three-dimensional petal-like morphology is obtained.

[0013] The substrate is then immersed in a copper salt solution, and through adsorption, drying and controlled thermal reduction, the copper ions interact with the pyridine nitrogen, pyrrole nitrogen and oxygen coordination groups on the substrate surface to form oxygen-pyrrole nitrogen co-modified nitrogen-doped carbon-supported copper single-atom coordination active centers.

[0014] Specifically, the cyano-containing olefinic unsaturated monomers include acrylonitrile, methacrylonitrile, ethyl acrylonitrile, or α-cyanoacrylate.

[0015] Specifically, the amount of acrylamide monomer added is 0.2wt% to 1wt% of the mass of the cyano-containing olefinic unsaturated monomer, the volume ratio of the cyano-containing olefinic unsaturated monomer and acrylamide monomer to the acetone is 1:0.5 to 2, and the volume ratio to azobisisobutyronitrile is 1:0.5 to 2.

[0016] The amount of acrylamide added is controlled at 0.2wt% to 1wt%. Adding a small amount of acrylamide monomer can regulate the amount of oxygen doping in the precursor and prevent the amide group from undergoing deamination reaction at high temperature, releasing NH3 and CO2, which would lead to excessive cross-linking. The nitrogen-doped carbon skeleton collapses due to excessive oxygen substitution of nitrogen sites, destroying the petal-like morphology.

[0017] Specifically, the heating reaction is carried out at a temperature of 60°C-70°C for 6-10 hours.

[0018] Specifically, the preset heating rate is 1℃ / min-10℃ / min, and the holding time is 2-4 hours.

[0019] A faster heating rate allows the system to quickly pass through the low-temperature range, shortening the reaction time of ionic cyclization. The ionic cyclization pathway is relatively suppressed, while the free radical cyclization pathway is promoted, causing the reaction to proceed in a direction more favorable to the formation of pyrrole nitrogen.

[0020] Specifically, the ratio of the pre-oxidized cyclized powder to the methanol is 50mg-200mg:10mL.

[0021] Specifically, the copper salt is divalent copper ions such as Cu(OAc)2·H2O, Cu(NO3)2, and CuCl2, and the mass ratio of the pre-oxidized cyclized powder to the copper salt is 100:2-10.

[0022] In nitrogen-doped carbon frameworks, pyridine nitrogen and oxygen sites are spatially dispersed, Cu 2+ The d orbital vacancies can form coordinate bonds with the lone pairs of electrons at the pyridine nitrogen and oxygen doping sites. The formation of coordinate bonds significantly increases the migration barrier of Cu, preventing it from migrating and agglomerating on the surface during subsequent thermal reduction, thus anchoring it to the substrate in the form of single atoms.

[0023] Specifically, the high-temperature carbonization temperature is 800℃-1000℃, and the holding time is 2 hours.

[0024] The second objective of this invention is to provide a petal-shaped oxygen-pyrrole nitrogen co-modified nitrogen-doped carbon copper single-atom catalyst, which is prepared using the above-described method for preparing petal-shaped oxygen-pyrrole nitrogen co-modified nitrogen-doped carbon copper single-atom catalyst.

[0025] The petal-shaped oxygen-pyrrole nitrogen co-modified nitrogen-doped carbon copper single-atom catalyst of the present invention is applied in an electrocatalytic reduction reaction, wherein the electrocatalytic reduction reaction includes at least one of nitrate reduction reaction, hydrogen evolution reaction or carbon dioxide reduction reaction.

[0026] (1) This invention uses polyacrylonitrile-acrylamide as a carbon precursor and achieves uniform loading of Cu single atoms on a nitrogen-doped carbon matrix through a process route of pre-oxidation cyclization-copper salt loading-high temperature carbonization. At the same time, oxygen doping effectively regulates the electronic structure of the nitrogen-doped carbon support and enhances the interaction between the catalyst and the reaction intermediate.

[0027] (2) The present invention can flexibly control the elemental composition and microstructure of the catalyst by adding acrylamide comonomer in the polymerization stage or adjusting the heating rate in the pre-oxidation cyclization stage, so as to achieve the controllable synthesis of a series of catalysts such as nitrogen-doped carbon-supported copper single atoms, oxygen-modified nitrogen-doped carbon-supported copper single atoms and oxygen-pyrrole nitrogen co-modified nitrogen-doped carbon-supported copper single atoms.

[0028] (3) By controlling the heating rate of the pre-oxidation cyclization stage, this invention successfully prepared a unique petal-shaped oxygen-pyrrole nitrogen co-modified nitrogen-doped carbon-supported copper single-atom electrocatalyst. This petal-shaped structure provides a larger specific surface area and more catalytic active sites, which is beneficial to the diffusion and adsorption of reactant molecules, thereby significantly improving the performance of electrocatalytic reduction. Taking nitrate reduction as an example, this catalyst can achieve better performance at -0.3 to -0.7 V. RHE Within the potential range, the average Faraday efficiency of ammonia remains stable at over 80%, and it exhibits excellent resistance to poisoning and structural stability, demonstrating great potential for practical applications. Attached Figure Description

[0029] Figure 1 XPS image of the petal-shaped oxygen-pyrrole nitrogen co-modified nitrogen-doped carbon supported copper single-atom catalyst prepared in Example 1 of this invention;

[0030] Figure 2 The N 1s XPS plot of the petal-shaped oxygen-pyrrole nitrogen co-modified nitrogen-doped carbon supported copper single-atom catalyst prepared in Example 1 of this invention;

[0031] Figure 3 This is a scanning electron microscope image of the petal-shaped oxygen-pyrrole nitrogen co-modified nitrogen-doped carbon-supported copper single-atom catalyst prepared in Example 1 of the present invention;

[0032] Figure 4 This is a STEM image of the petal-shaped oxygen-pyrrole nitrogen co-modified nitrogen-doped carbon-supported copper single-atom catalyst prepared in Example 1 of this invention;

[0033] Figure 5 A scanning electron microscope image of the petal-shaped nitrogen-doped carbon-supported copper single-atom catalyst prepared in Comparative Example 1 of this invention.

[0034] Figure 6This is a scanning electron microscope image of the petal-shaped oxygen-modified nitrogen-doped carbon-supported copper single-atom catalyst prepared in Comparative Example 2 of the present invention.

[0035] Figure 7 This is a scanning electron microscope image of the non-petal-shaped oxygen-pyrrole nitrogen co-modified nitrogen-doped carbon supported copper single-atom catalyst prepared in Comparative Example 3 of the present invention.

[0036] Figure 8 The nitrogen isothermal adsorption-desorption curve of the petal-shaped oxygen-pyrrole nitrogen co-modified nitrogen-doped carbon supported copper single-atom catalyst prepared in Example 1 of this invention;

[0037] Figure 9 Linear sweep voltammetric curves of the petal-shaped oxygen-pyrrole nitrogen co-modified nitrogen-doped carbon supported copper single-atom catalysts prepared in Example 1, Comparative Example 1, and Comparative Example 2 of this invention in the electrocatalytic nitrate reduction reaction;

[0038] Figure 10 The bar chart shows the Faraday efficiency of the petal-shaped oxygen-pyrrole nitrogen co-modified nitrogen-doped carbon-supported copper single-atom catalysts prepared in Examples 1-3 of this invention in the catalytic reduction reaction of nitrate to generate ammonia at different potentials. Detailed Implementation

[0039] To make the objectives, technical solutions, and effects of this invention clearer and more explicit, the invention is further described in detail below. It should be understood that the specific embodiments described herein are only for explaining the invention and are not intended to limit the invention. All substances in the examples and comparative examples are of analytical grade.

[0040] Example 1: Preparation of petal-shaped oxygen-pyrrole nitrogen co-modified nitrogen-doped carbon supported copper single-atom catalyst.

[0041] (1) Preparation of copolymer powder: 2 mL of acrylonitrile monomer and 0.2 wt% of acrylamide comonomer were dissolved in 2 mL of acetone, and 2 mg of azobisisobutyronitrile was added as an initiator. The reaction was carried out at 70 °C for 6 hours under argon protection to perform free radical copolymerization. After the reaction was completed, the white copolymer powder containing oxygen polyacrylonitrile was obtained by vacuum drying.

[0042] (2) Pre-oxidation cyclization treatment: The copolymer powder is subjected to pre-oxidation cyclization treatment in air atmosphere, heated to 230°C at a heating rate of 5°C / min, and held for 2 hours to obtain brown powder.

[0043] (3) Copper salt loading: Take 50 mg of the obtained brown powder, disperse it in 10 mL of methanol, ultrasonically disperse it, add 5 mg of CuCl2, and stir at room temperature for 6 hours. Then remove the solvent by rotary evaporation to obtain the copper salt loaded precursor.

[0044] (4) High-temperature carbonization: The obtained precursor was placed in a tube furnace and carbonized at 900°C for 2 hours under argon atmosphere protection. It was then naturally cooled to room temperature to obtain Cu-NC catalyst.

[0045] like Figure 1-2 As shown, oxygen and pyrrole nitrogen have been successfully introduced into nitrogen-doped carbon substrates. Figure 3 As shown, it exhibits a distinct petal-like morphology, with a particle size of approximately 1.2 μm. (As...) Figure 4 As shown, copper single atoms (marked by red circles) are uniformly anchored on the substrate, and no metal clusters are generated.

[0046] Example 2: Preparation of petal-shaped oxygen-pyrrole nitrogen co-modified nitrogen-doped carbon supported copper single-atom catalyst.

[0047] (1) Preparation of copolymer powder: 2 mL of acrylonitrile monomer and 0.5 wt% of acrylamide comonomer were dissolved in 3 mL of acetone, and 1.5 mg of azobisisobutyronitrile was added as an initiator. The reaction was carried out at 60 °C for 8 hours under argon protection to perform free radical copolymerization. After the reaction was completed, the white copolymer powder containing oxygen polyacrylonitrile was obtained by vacuum drying.

[0048] (2) Pre-oxidation cyclization treatment: The copolymer powder is subjected to pre-oxidation cyclization treatment in an air atmosphere, heated to 220°C at a heating rate of 2°C / min, and held for 2 hours to obtain brown powder.

[0049] (3) Copper salt loading: 100 mg of the obtained brown powder was dispersed in 10 mL of methanol, ultrasonically dispersed, and then 8 mg of CuCl2 was added. The mixture was stirred at room temperature for 6 hours. The solvent was then removed by rotary evaporation to obtain the copper salt-loaded precursor.

[0050] (4) High-temperature carbonization: The obtained precursor was placed in a tube furnace and carbonized at 800°C for 2 hours under argon atmosphere protection. It was then naturally cooled to room temperature to obtain Cu-NC catalyst.

[0051] Example 3: Preparation of petal-shaped oxygen-pyrrole nitrogen co-modified nitrogen-doped carbon supported copper single-atom catalyst.

[0052] (1) Preparation of copolymer powder: 2 mL of acrylonitrile monomer and 1 wt% of acrylamide comonomer were dissolved in 3 mL of acetone, and 3 mg of azobisisobutyronitrile was added as an initiator. The reaction was carried out at 70 °C for 10 hours under argon protection to perform free radical copolymerization. After the reaction was completed, the white copolymer powder containing oxygen polyacrylonitrile was obtained by vacuum drying.

[0053] (2) Pre-oxidation cyclization treatment: The copolymer powder is subjected to pre-oxidation cyclization treatment in air atmosphere, and the temperature is raised to 230°C at a heating rate of 1°C / min and held for 2 hours to obtain brown powder.

[0054] (3) Copper salt loading: Take 200 mg of the obtained brown powder, disperse it in 10 mL of methanol, ultrasonically disperse it, add 10 mg of CuCl2, and stir at room temperature for 6 hours. Then remove the solvent by rotary evaporation to obtain the copper salt loaded precursor.

[0055] (4) High-temperature carbonization: The obtained precursor was placed in a tube furnace and carbonized at 900°C for 2 hours under argon atmosphere protection. It was then naturally cooled to room temperature to obtain Cu-NC catalyst.

[0056] The percentage content of different types of nitrogen in Examples 1-3 is shown in Table 1:

[0057] Table 1: Percentage content (at%) of different types of nitrogen in Examples 1-3

[0058] Example Pyridine nitrogen Pyrrole nitrogen Graphite nitrogen Oxidized nitrogen Example 1 26.0 25.9 37.5 10.6 Example 2 29.0 21.9 41.1 8.0 Example 3 28.7 21.2 41.7 8.4

[0059] Comparative Example 1: Preparation of petal-shaped nitrogen-doped carbon-supported copper single-atom catalyst.

[0060] (1) Preparation of copolymer powder: 2 mL of acrylonitrile monomer was dissolved in 2 mL of acetone, and 2 mg of azobisisobutyronitrile was added as an initiator. The reaction was carried out at 70 °C for 8 hours under argon protection to perform free radical polymerization. After the reaction was completed, the polyacrylonitrile was dried under vacuum to obtain a white powder.

[0061] (2) Pre-oxidation cyclization treatment: The obtained white polyacrylonitrile powder was subjected to pre-oxidation cyclization treatment in air atmosphere, and the temperature was raised to 230℃ at a heating rate of 0.1℃ / min and held for 2 hours to obtain brown powder.

[0062] (3) Copper salt loading: 100 mg of the obtained brown powder was dispersed in 10 mL of methanol, ultrasonically dispersed, and then 8 mg of CuCl2 was added. The mixture was stirred at room temperature for 6 hours. The solvent was then removed by rotary evaporation to obtain the copper salt-loaded precursor.

[0063] (4) High-temperature carbonization: The obtained precursor was placed in a tube furnace and carbonized at 900°C for 2 hours under argon atmosphere protection. It was then naturally cooled to room temperature to obtain Cu-NC catalyst.

[0064] like Figure 5 As shown, it has a distinct petal-like morphology and a particle size of approximately 1.3 μm.

[0065] Comparative Example 2: Preparation of petal-shaped oxygen-modified nitrogen-doped carbon-supported copper single-atom catalyst.

[0066] (1) Preparation of copolymer powder: 2 mL of acrylonitrile monomer and 0.2 wt% of acrylamide comonomer were dissolved in 2 mL of acetone, and 2 mg of azobisisobutyronitrile was added as an initiator. The reaction was carried out at 70 °C for 8 hours under argon protection to perform free radical copolymerization. After the reaction was completed, the oxygen-containing polyacrylonitrile copolymer was dried under vacuum to obtain a white powder.

[0067] (2) Cycloning treatment: Take 500 mg of the above oxygen-containing polyacrylonitrile copolymer white powder, heat it to 230°C at a heating rate of 0.1°C / min, and keep it at the temperature for 2 hours to obtain brown-black powder.

[0068] (3) Copper salt loading: 100 mg of the obtained brown-black powder was dispersed in 10 mL of methanol, ultrasonically dispersed, and then 8 mg of CuCl2 was added. The mixture was stirred at room temperature for 6 hours. The solvent was then removed by rotary evaporation to obtain the copper salt-loaded precursor.

[0069] (4) High-temperature carbonization: The obtained precursor was placed in a tube furnace and carbonized at 900°C for 2 hours under argon atmosphere protection. It was then naturally cooled to room temperature to obtain Cu-NC catalyst.

[0070] like Figure 6 As shown, it has a distinct petal-like morphology and a particle size of about 1.2 μm.

[0071] Comparative Example 3: Preparation of a non-petal-shaped oxygen-pyrrole nitrogen co-modified nitrogen-doped carbon-supported copper single-atom catalyst.

[0072] (1) Preparation of copolymer powder: 2 mL of acrylonitrile monomer and 1.5 wt% of acrylamide comonomer were dissolved in 3 mL of acetone, and 4 mg of azobisisobutyronitrile was added as an initiator. The reaction was carried out at 70 °C for 10 hours under argon protection to perform free radical copolymerization. After the reaction was completed, the oxygen-containing polyacrylonitrile copolymer was dried under vacuum to obtain a white powder.

[0073] (2) Cycloning treatment: Take 500 mg of the above oxygen-containing polyacrylonitrile copolymer white powder, heat it to 240°C at a heating rate of 10°C / min, and keep it at the temperature for 2 hours to obtain brown-black powder.

[0074] (3) Copper salt loading: Take 200 mg of the obtained brown-black powder, disperse it in 10 mL of methanol, and after ultrasonic dispersion, add 10 mg of CuCl2 and stir at room temperature for 6 hours. Then remove the solvent by rotary evaporation to obtain the copper salt loaded precursor.

[0075] (4) High-temperature carbonization: The obtained precursor was placed in a tube furnace and carbonized at 1000℃ for 2 hours under argon atmosphere protection. It was then naturally cooled to room temperature to obtain Cu-NC catalyst.

[0076] like Figure 7As shown, the petal-like morphology has been destroyed, the thin-layer structure has collapsed, and the active area will be reduced.

[0077] The prepared catalysts were coated onto the surface of carbon paper electrodes as working electrodes, with an Ag / AgCl electrode as the reference electrode and a platinum sheet as the counter electrode. Electrocatalytic nitrate reduction was tested in an electrolyte containing nitrates. Test conditions: The electrolyte was a 1 mol / L potassium hydroxide solution containing a certain concentration of potassium nitrate. Electrochemical tests were performed using potentiostatic or linear sweep voltammetry. After the reaction, the concentrations of nitrite and ammonia in the solution were determined by UV-Vis spectrophotometry or ion chromatography, and the ammonia Faradaic efficiency and yield were calculated.

[0078] refer to Figure 8 The figure shows the nitrogen isothermal adsorption-desorption curve of the petal-shaped oxygen-pyrrole nitrogen co-modified nitrogen-doped carbon-supported copper single-atom catalyst prepared in Example 1. This curve exhibits typical Type IV isotherm characteristics, with a significant hysteresis loop appearing in the high relative pressure range, demonstrating that the oxygen-pyrrole nitrogen co-modified nitrogen-doped carbon-supported copper single-atom material simultaneously possesses microporous and mesoporous structures. When the relative pressure approaches 1.0, the total saturated nitrogen adsorption capacity of the material reaches 614.9 cm³. 3 / g indicates that the material has a rich pore structure and a large total pore volume.

[0079] refer to Figure 9 Linear sweep voltammetry (LSV) curves of the petal-shaped oxygen-pyrrole nitrogen co-modified nitrogen-doped carbon-supported copper single-atom catalysts prepared in Examples 1, 1, and 2 for the electrocatalytic nitrate reduction reaction are shown. The solid red line represents the test curve for the electrolyte containing nitrate, and the dashed red line represents the background curve for the blank electrolyte without nitrate. The cathodic reduction current density significantly increased after the introduction of nitrate, demonstrating that the oxygen-pyrrole nitrogen co-modified nitrogen-doped carbon-supported copper single-atom catalysts have excellent catalytic activity for the electrocatalytic nitrate reduction reaction.

[0080] refer to Figure 10 The bar chart shows the Faraday efficiency of the petal-shaped oxygen-pyrrole nitrogen co-modified nitrogen-doped carbon-supported copper single-atom catalysts prepared in Examples 1-3 for ammonia production in the electrocatalytic nitrate reduction reaction at different potentials. The prepared catalyst materials exhibited Faraday efficiency at potentials ranging from -0.3 to -0.7 V. RHE All ranges achieved ammonia Faraday efficiencies higher than 80%, with the catalyst material prepared in Example 1 achieving efficiencies from -0.3 to -0.7 V. RHE All intervals achieved an ammonia faradaic efficiency of over 90%.

[0081] It should be understood that the application of the present invention is not limited to the examples above. Those skilled in the art can make improvements or modifications based on the above description, and all such improvements and modifications should fall within the protection scope of the appended claims.

Claims

1. A method for preparing a petal-shaped oxygen-pyrrole nitrogen co-modified nitrogen-doped carbon-supported copper single-atom catalyst, characterized in that, The method for preparing the catalyst includes the following steps: A free radical copolymerization reaction was carried out in acetone using cyano-containing olefinic unsaturated monomers and acrylamide monomers, with azobisisobutyronitrile as the initiator. The reaction was carried out under inert gas protection and the reaction was heated. After the reaction was completed, the copolymer powder was obtained by drying. The copolymer powder is subjected to pre-oxidation cyclization treatment by raising the temperature to the pre-oxidation temperature at a preset heating rate and holding it at the temperature, so that the copolymer powder undergoes cyclization crosslinking and stabilization reactions to obtain pre-oxidized cyclized powder. The pre-oxidized cyclized powder was dispersed in methanol, copper salt was added, and after stirring and mixing, the solvent was removed to obtain the precursor. The precursor was subjected to high-temperature carbonization under inert gas protection to obtain a petal-shaped oxygen-pyrrole nitrogen co-modified nitrogen-doped carbon-supported copper single-atom catalyst.

2. The method for preparing the petal-shaped oxygen-pyrrole nitrogen co-modified nitrogen-doped carbon-supported copper single-atom catalyst according to claim 1, characterized in that, The cyano-containing olefinic unsaturated monomers include acrylonitrile, methacrylonitrile, ethylacrylonitrile, or α-cyanoacrylate.

3. The method for preparing the petal-shaped oxygen-pyrrole nitrogen co-modified nitrogen-doped carbon-supported copper single-atom catalyst according to claim 1, characterized in that, The amount of acrylamide monomer added is 0.2wt% to 1wt% of the mass of the cyano-containing olefinic unsaturated monomer, the volume ratio of the cyano-containing olefinic unsaturated monomer and acrylamide monomer to the acetone is 1:0.5 to 2, and the amount ratio of acrylamide monomer to azobisisobutyronitrile is 1mL:0.5mg to 2mg.

4. The method for preparing a petal-shaped oxygen-pyrrole nitrogen co-modified nitrogen-doped carbon-supported copper single-atom catalyst according to claim 1, characterized in that, The heating reaction is carried out at a temperature of 60℃-70℃ for 6-10 hours.

5. The method for preparing a petal-shaped oxygen-pyrrole nitrogen co-modified nitrogen-doped carbon-supported copper single-atom catalyst according to claim 1, characterized in that, The pre-oxidation temperature is 220-240℃, the preset heating rate is 1℃ / min-10℃ / min, and the holding time is 2-4 hours.

6. The method for preparing a petal-shaped oxygen-pyrrole nitrogen co-modified nitrogen-doped carbon-supported copper single-atom catalyst according to claim 1, characterized in that, The ratio of the pre-oxidized cyclized powder to the methanol is 50mg-200mg:10mL.

7. The method for preparing a petal-shaped oxygen-pyrrole nitrogen co-modified nitrogen-doped carbon-supported copper single-atom catalyst according to claim 1, characterized in that, The copper salt is Cu(OAc)2·H2O, Cu(NO3)2, or CuCl2, and the mass ratio of the pre-oxidized cyclized powder to the copper salt is 100:2-10.

8. The method for preparing a petal-shaped oxygen-pyrrole nitrogen co-modified nitrogen-doped carbon-supported copper single-atom catalyst according to claim 1, characterized in that, The high-temperature carbonization temperature is 800℃-1000℃, and the holding time is 2 hours.

9. A petal-shaped oxygen-pyrrole nitrogen co-modified nitrogen-doped carbon-supported copper single-atom catalyst, characterized in that, It was prepared using the method for preparing petal-shaped oxygen-pyrrole nitrogen co-modified nitrogen-doped carbon copper single-atom catalyst as described in any one of claims 1 to 8.

10. The application of the petal-shaped oxygen-pyrrole nitrogen co-modified nitrogen-doped carbon-supported copper single-atom catalyst as described in claim 9, characterized in that, It is used in electrocatalytic reduction reactions, wherein the electrocatalytic reduction reaction includes at least one of nitrate reduction reaction, hydrogen evolution reaction or carbon dioxide reduction reaction.